Design of a novel procedure for the optimization of the mechanical performances of 3D printed scaffolds for bone tissue engineering combining CAD, Taguchi method and FEA. (July 2019) - Marchiori, Gregorio; Berni, Matteo; Boi, Marco; Petretta, Mauro; Grigolo, Brunella; Bellucci, Devis; Cannillo, Valeria; Garavelli, Chiara; Bianchi, Michele
Highlights: This study aims to reduce time and costs of scaffolds manufacturing and testing. A novel design procedure is provided to fabricate only the most promising scaffolds. The novel scaffold design combines for the first time CAD, Taguchi method and FEA. The proposed design controls scaffold geometry, material, porosity and stiffness. It is applied to precision extrusion deposition of novel PCL/bioactive glass scaffolds. Abstract: In order to increase manufacturing and experimental efficiency, a certain degree of control over design performances before realization phase is recommended. In this context, this paper presents an integrated procedure to design 3D scaffolds for bone tissue engineering. The procedure required a combination of Computer Aided Design (CAD), Finite Element Analysis (FEA), and Design methodologies Of Experiments (DOE), firstly to understand the influence of the design parameters, and then to control them. Based on inputs from the literature and limitations imposed by the chosen manufacturing process (Precision Extrusion Deposition), 36 scaffold architectures have been drawn. The porosity of each scaffold has been calculated with CAD. Thereafter, a generic scaffold material was considered and its variable parameters were combined with the geometrical ones according to the Taguchi method, i.e. a DOE method. The compressive response of those principal combinations was simulated by FEA, and the influence of each design parameter on the scaffold compressive behaviour was clarified. Finally, a regression model was obtained correlating the scaffold's mechanical performances to its geometrical and material parameters. This model has been applied to a novel composite material made of polycaprolactone and innovative bioactive glass. By setting specific porosity (50%) and stiffness (0.05 GPa) suitable for trabecular bone substitutes, the model selected 4 of the 36 initial scaffold architectures. Only these 4 more promising geometries will be realized and physically tested for advanced indications on compressive strength and biocompatibility.